ANALISIS KOMPONEN WEBSITE DESA WISATA CIMANDE SEBAGAI MEDIA PROMOSI ELEKTRONIK (E-TOURISM) - Dhanik Puspita Sari; Rima Pratiwi Batubara (Universitas Djuanda Bogor, 2021)
Nowadays, promotion via the internet is considered easier to do. In addition to lower costs, the use of the internet for promotion is considered more real time and more informative because it can convey information precisely and clearly. Cimande Tourism Village uses a website to promote its tourism activities (e-tourism). However, the existing website is not well managed and needs to be repaired and updated. The research was conducted with a qualitative approach to find out various problems with the tourism promotion website of the Cimande Tourism Village. This study identifies website components using indicators, namely domain name, year of creation, website, website credibility and functionality and the quality of website content presentation. In the research, the results show that the Cimande Tourism Village website has a domain name, namely desawisatacimande.com. Domains are included in the generic Top Level Domain (gTLD) and do not use country codes because they are non-formal and commercial. The website was created on 27 December 2019. The type of website is included in the static website and the website owner is RUMAHOSTING.COM. The copyright is owned by Cimande Tourism Village with data citation so far not available. Updates on the website are classified as minimal because the manager has not made it a habit of procuring (scheduling) updates on the website. The menu bar on the website can be found on the website home page and the website navigation function works well. A quick search is provided by the website but the quality is still poor. Site map is available in the contact section of the website. The color contrast on the website is considered good and the use of foreign languages is still not there.